Estimation of breeding values of first lactation 305-day milk yield from single and multi-trait animal models in Karan Fries cattle - P, DIVYA; SINGH, AVTAR; GANDHI, R S; SINGH, R K (The Indian Journal of Animal Sciences, 2014)
First lactation data on 528 cows sired by 98 sires maintained at National Dairy Research Institute, Karnal over a period of 26 years (1986–2011) were used to estimate heritability and breeding value of the first lactation 305- day or less milk yield and 4 fertility traits like age at first calving (AFC), first service period (FSP), first calving interval (FCI) and cow pregnancy rate (CPR) using single and multi-trait models with the help of WOMBAT software. The heritability of FL305DMY was 0.235 using single trait animal models, 0.223, 0.213, 0.196 and 0.147 from 2 trait analysis with FCI, FSP, AFC and CPR respectively. In 3 trait analysis (FL305DMY-FCI- AFC) heritability FL305DMY was 0.199. There were marginal deviations in heritability estimates of fertility traits also, from single trait to multiple trait estimation combining milk production. The Spearman’s rank correlations between rankings based on estimated breeding values (EBVs) of FL305DMY from single trait (only FL305DMY) animal model with 2 traits (FL305DMY-AFC, FL305DMY-FCI and FL305DMY-FSP) and 3 traits (FL305DMY-AFC-FCI) animal models were 0.86, 0.92, 0.94 and 0.82 respectively. It was inferred that if the Karan Fries cows are culled exclusively on the basis of EBVs estimated from single trait analysis, the culling decision will be erroneous. Further, the study on lowest ranking 100 cows (20% of data) which are generally culled from the herd revealed that 59 - 65% of the cows which were poor only in FL305DMY would be culled irrespective of their superiority in reproductive traits.